Sovereign attachments : masculinity, Muslimness, and affective politics in Pakistan - Khoja-Moolji, Shenila, 1982- (University of California Press, 2021)
"Sovereign Attachments rethinks sovereignty by moving it out of the exclusive domain of geopolitics and legality, and into cultural, religious, and gender studies. Through a close reading of a stunning array of cultural texts produced by the Pakistani state and the Pakistan-based Taliban, Khoja-Moolji theorizes sovereignty as an ongoing attachment negotiated in public culture. Both the state and the Taliban recruit publics into relationships of trust, protection, and fraternity by summoning models of Islamic masculinity, mobilizing kinship metaphors, and marshalling affect. In particular, masculinity and Muslimness emerge as salient performances through which sovereign attachments are harnessed. The book shifts the discussion of sovereignty away from questions around absolute dominance to ones about shared repertoires, entanglements, and co-constitution"--